(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
This study aimed to know the effect of Pinching on the growth of seedlings carob developing in containers Minirhizotron. Where we are cutting the top of main root at different lengths : 1- at 3 cm (C3) 2- at 6 cm (C6) 3- at 9 cm (C9) 4- without cutting – control - (C0) and studied several quantities indicators of growth and development of the total shoot and root of the seedlings for a period of three months. For the treatment (C3) we are noticed that the all seedling were die. For a radical system, results indicated a high significant superiority in the treatment (C0) values ​​for the main root of the overall growth rate such as length (cm) and the speed of growth (cm/3days) height to treatment (C6 and C9).for another sight (C6) has a high significant superiority upon the treatment C9 and control treatment at the dry weight of root system. regarding to shoot system a significant state has dominated for the treatment (C6) at the other treatments (C9 – C0) in some indicators such as average height and average the dry weight of shoots . هدفت الدراسة إلى معرفة تأثير قطع القمة النامية للجذر الرئيس على نمو بادرات الخرنوب المزروعة ضمن أوعية الميني ريزوترونات. تمّ قطع الجزء الطرفي بطول 1 سم من قمة الجذر الرئيس بعد أن بلغ أطوال مختلفة, حيث قطع عند طول 3 سم ( C3 ) وطول 6 سم ( C6 ) وطول 9 سم ( C9 ) أمّا معاملة الشاهد فبقيت دون قطع (C0). ودرست عدة مؤشرات كميّة خاصة بنمو وتطور المجموع الخضري والجذري للبادرات ولمدة ثلاثة أشهر . تم تسجيل موت جميع البادرات بالنسبة لمعاملة القطع ( C3 ) مباشرة بعد مضي فترة 3 – 6 أيام . بالنسبة للجهاز الجذري, أشارت النتائج إلى تفوق معنوي عالٍ في قيم معاملة الشاهد الخاصة بمعدل نمو الجذر الرئيس كالطول الكلي (سم) وسرعة النمو (سم/3 أيام ) على معاملتي القطع ( C6 و C9 ) . ومن ناحية أخرى فقد تفوقت معالمة القطع ( C6 ) على معاملة القطع C9 ومعاملة الشاهد بالقيم الخاصة بالوزن الجاف للمجموع الجذري. بالنسبة للمجموع الهوائي, فقد سادت حالة التفوق المعنوي لمعاملة القطع ( C6 ) على المعاملتين الباقيتين بخصوص بعض المؤشرات المتعلقة بالساق كمتوسط الطول وفي متوسط القطر ومتوسط الوزن الجاف للمجموع الخضري أيضاً.